Transient expression and purification of S2 protein from porcine epidemic diarrhea virus in plants - Ho, Thuong Thi; Trinh, Vy Thai; Hoang, Hang Thi Thu; Pham, Ngoc Bich; Chu, Ha Hoang (Vietnam Journal of Biotechnology, 2022)
Porcine epidemic diarrhea (PED), caused by the Porcine epidemic diarrhea virus (PEDV), is an acute, highly contagious disease of pigs of all ages, especially piglets under one week old, with the mortality rate reaching 95–100%. Developing an effective vaccine against PEDV in Vietnam is urgent. Spike protein containing S1 and S2 subunits is considered the main target for vaccine development, and the S2 subunit contains immunodominant neutralizing epitopes of PEDV. To date, the expression of S2 protein in plants has not been reported and evaluated. In this study, the gene encoding the S2 subunit of a PEDV strain belonging to genotype 2a was amplified, sequenced, and inserted in a pRTRA vector containing the GCN4pII (pII) motif. The plant expression cassette containing S2-pII was then inserted into the pCB301 vector. The Agrobacterium tumefaciens harboring the pCB301-S2-pII vector was transformed into Nicotiana benthamiana leaves via agroinfiltration. The accumulation level of S2-pII protein in tobacco leaves was semi-quantified by Western blot, accounting for approximately 86.7 mg/kg of fresh leaves and 1.47% total soluble protein, which was 294-fold higher than the accumulation level of S1-pII protein in our previous publication. S2-pII protein was successfully purified by immobilized metal affinity chromatography (IMAC). The oligomeric state of S2-pII protein was characterized by size exclusion chromatography (SEC). The S2-pII protein was determined to be a multimer protein with a high molecular weight. These results are the basis for more extended studies to develop a plant-based S2 vaccine against PEDV infection.